Políticas educacionais e prática docente: Comunidade Quilombola Sítio Alto, Simão Dias, Sergipe - Souza, Carleandro de Jesus (2024)
This research has as its theme the Educational Policies and Teaching Practice: Quilombola Community Sítio Alto, Simão Dias/SE, and its object of study is the Educational Policies and Education in the Countryside. The research is linked to the Federal University of Sergipe, to the Postgraduate Program in Education, in the line of research Training and Teaching Practice, also linked to the Research Group Education and Social Movements (GPEMS) and to the project Educational Policies, Teacher Training and Quality of Teaching in Basic Education. This project aims to analyze the contributions of the National Program for Rural Education (Pronacampo) in the public education systems, in the training of teachers, as well as in the management of rural and quilombola schools. The research was developed in a Remnant Quilombo Community (CRQ) and in a school of the final years of Elementary School (6th to 9th grade), which serves students of this community, located in the rural area of the municipality of Simão Dias/SE. The study was based on the following research problem: To what extent do the actions implemented in teaching practice reflect the principles described in the National Curricular Guidelines for Quilombola School Education in Basic Education, aimed at the local quilombola community? The general objective was to analyze the teaching practice of teachers in the education of students from the Remnant Quilombo Community (CRQ) Sítio Alto, considering the educational policies for Quilombola School Education. As specific objectives, we sought to address the main educational policies aimed at quilombola communities and their implementation in the quilombola community of Sítio Alto; to reflect on teaching practice and its relationship with the sociocultural and territorial peculiarities of the quilombola community of Sítio Alto; and to identify the difficulties and obstacles in the implementation of pedagogical actions for quilombola education, considering teaching planning. This study is a qualitative research in its approach. The research is a case study, in which the teaching practice for quilombola students was investigated. Data collection was carried out through documentary analysis of the municipal Curricular Matrix, the institutional Pedagogical Political Project (PPP) and the teachers' annual planning. In addition, semistructured interviews and focus groups were conducted. Through the analytical process, conducted by Discursive Textual Analysis (DTA), we concluded that, although there are approaches to aspects inherent to CRQ Sítio Alto in the educational processes of the Genésio Chagas Municipal School, we observed that these approaches are superficial. Aspects related to this community, such as reminiscent languages, collective memory and cultural practices, represented by circle dancing and musicality, are not worked on in the daily teaching practice. In addition, we concluded that there is a shortage of educational policies, mainly at the municipal level, directed at CRQ Sítio Alto, which promote the recovery of memory and cultural practices and which emphasize the importance of educational practice being aligned with the specificities of these peoples. In general terms, the type of education offered to quilombola students does not meet the principles of Quilombola School Education, defined in Resolution No. 8, of November 20, 2012.